PENGARUH PEMBERIAN KOMBINASI EMULSI® DAN MINYAK ATSIRI TEMULAWAK (Curcuma xanthorrhiza Roxb.) TERHADAP BERAT BADAN, ASUPAN MAKANAN DAN MINUMAN TIKUS PUTIH JANTAN GALUR WISTAR YANG DITEKAN NAFSU MAKANNYA - , MERINDRY EKA AYU WULANDARI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Temulawak (Curcuma xanthorrhiza Roxb) has been studied containing essential oil responsible in increasing appetite due to its choleretic characteristic that stimulate lever to produce more gall liquid to speed digestion and fat absorption in intestine so stomach emptying occur faster. This research was intended to identify effect of development of body weight, food and drink intake of male white mice of wistar strain with pressed appetite with diethylpropion HCl after treatment of Emulsi® and temulawak essential oil. Temulawak essential oil is obtained by distillation of vapor and water. Combination of 4.725 ml/kg bw Emulsi® and 0.044 ml/kg bw temulawak essential oil was given with volume ratios 100:0, 67:33, 50:50, 33:67, 0:100. Then the combination is administered orally on with pressed appetite. Result of average test of body weight per seven day, food and drink intake was analyzed using one way Anova and post hoc Tukey HSD test. Result of the research indicated that administering combination of 4.725 ml/kg bw Emulsi® and 0.044 ml/kg bw temulawak essential oil with volume ratio of 50:50 and 0:100 can increase mice body weight given with appetite pressure but work most optimal in day seven using the combination. However, it cannot increase food intake of mice with pressed appetite. In ratio 33:67, it can increase drink intake of pressed-appetite mice.